Prevalence and Predictors of Affirmations of Intimate Partner Violence in Germany: A First Nationwide Study on Victimization in Women and Men - Jud, Andreas (Journal of interpersonal violence, 2023)
Large-size studies on the prevalence of female intimate partner violence (IPV) victimization in Germany are rare and partly outdated; representative data on male IPV victimization are lacking altogether. The present survey addresses these gaps. For this study, the instrument of the WHO Multi-country study on women’s health and domestic violence has been translated to German and adapted to be used with females and males. A random route procedure in selecting household addresses has been used to gather data on IPV in combination with an omnibus survey on (mental) health issues. A total 2,503 respondents with a minimum age of 14 years have participated (response rate=44.1%). The resulting distribution of age and gender was representative for the German population above the age of 14 years. A total of 57.6% of female participants and 50.8% of male participants have reported victimization by intimate partners during their lifespan; gender distribution differs significantly (Chi2=43.43; p<0.001). Out of the different documented subtypes, psychological IPV was most prevalent (53.6% in females, 48.0% in males). Other forms ranged between 15.2% (physical IPV) and 18.6% (sexual IPV) for females, and 5.5% (sexual IPV) and 10.8% (physical IPV) for males. All forms of victimization regularly coincided, both in females and males. Experiencing any IPV was not only significantly associated with female gender, but also with older age, periods of unemployment, poverty, and IPV perpetration. The findings highlight the still much needed global efforts to prevent IPV against women – and in general. They further support previous research in underlining that fighting poverty might also be instrumental in reducing the likelihood of IPV. The discussion further addresses the issues of reciprocity in IPV.